Trusted storage mechanism of distributed electric energy data based on blockchain - Jin LI; Songqi WU; Senlin ZHANG; Yueming LU (网络与信息安全学报)
Facing the problems of central single point failure and malicious tampering in the centralized storage of electric energy data,a trusted storage mechanism including identity authentication,sensor data upload,IPFS storage,blockchain upload and access verification was proposed by building the inter satellite storage consortium blockchain (ISCB) of electric energy data based on the decentralized,tamper proof and highly expandable characteristics of blockchain.In view of the characteristics of electric energy data,such as wide source and large capacity,the blockchain technology was combined with the inter planetary file system (IPFS),and the data hash and query attributes returned by IPFS were saved on the chain,so as to effectively solve the problems of storage expansion and data tampering identification of electric energy data blockchain.